1991
DOI: 10.1111/j.1365-2362.1991.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscarinic blockade on insulin secretion and on glucose‐induced thermogenesis in lean and obese human subjects

Abstract: To determine whether hyperinsulinaemia of human obesity is dependent on the activity of the parasympathetic nervous system, and whether activation of the parasympathetic nervous system plays a role in glucose-induced thermogenesis, the metabolic effect of a continuous intravenous glucose infusion [44.4 mumol kg-1 body weight (bw) min-1] with or without atropine infusion was assessed in 11 obese patients and 10 lean controls. Compared with lean controls, obese patients had increased basal and glucose-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…This consideration is based on a previous study in healthy women in which infusions of trimethaphan or atropine after no meal was ingested resulted in no changes in baseline insulin or glucose levels (B.A., unpublished observations). Similarly, it has been shown previously that atropine does not affect baseline insulin or glucose levels in humans (10,36,37). This consideration is also supported by the absence of any change in basal insulin and glucose levels during the 15 or 10 min preceding meal ingestion, but after administration of trimethaphan or atropine in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…This consideration is based on a previous study in healthy women in which infusions of trimethaphan or atropine after no meal was ingested resulted in no changes in baseline insulin or glucose levels (B.A., unpublished observations). Similarly, it has been shown previously that atropine does not affect baseline insulin or glucose levels in humans (10,36,37). This consideration is also supported by the absence of any change in basal insulin and glucose levels during the 15 or 10 min preceding meal ingestion, but after administration of trimethaphan or atropine in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In the subset of obese subjects, fasting leptin levels were also significantly elevated, but no significant differences were found between the two populations for PP. During the 30-min period before meal ingestion, atropine administration significantly lowered plasma glucagon in both the lean and obese subjects but had no effect on basal levels of plasma insulin or glucose (Table 2), supporting findings by other investigators (7,41).…”
Section: R199 Early Phase Insulin Supplementation In Obese and Lean Ssupporting
confidence: 84%
“…The increase in preabsorptive insulin is thought to be a reflection of increased PNS activity, exhibited in many animal models of obesity (22,31,39). However, in humans there is little evidence supporting an increase in PNS activity at the level of the pancreas (24,41). Furthermore, we (53) and other investigators (46) have suggested that increases in preabsorptive insulin release in obesity are merely a reflection of increased basal insulin levels.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, very limited data exist to support the hypothesis of a neural mechanism underlying the effects of GLP-1 in humans. In humans, a selective block of afferent vagal transmission is not easily accomplished, but efferent activity may be blocked by using either a ganglionic blocker or atropine (2,4,44,46). The present study was designed to investigate the role of efferent vagal, muscarinic activity for the insulinotropic and glucagonostatic effects of GLP-1.…”
mentioning
confidence: 99%